Kinetics and Mechanism of Oxidation of 2-(2-Methoxyethoxy)ethanol and 2-(2-Ethoxyethoxy)ethanol by Ditelluratoargentate(III) in Alkaline Medium - Shan, Jinhuan; Han, Jin; Li, Yi; Zhang, Ziwei (Asian Journal of Chemistry, 2014)
Oxidation of 2-(2-methoxyethoxy)ethanol and 2-(2-ethoxyethoxy)ethanol by ditelluratoargentate(III) in alkaline liquids has been studied spectrophotometrically in the temperature range of 293.2 - 313.2 K. The first-order rates with respect to reductant and Ag(III) were all found. It was found that the pseudo-first-order rate constant kobs increased with an increase in concentration of OH- and a decrease in concentration of H4TeO62-. There was a positive salt effect and no free radicals were detected. In view of this, the Ag(H3TeO6)(H2O)2 is assumed to be the active species. A plausible mechanism is proposed and the rate equations derived from the mechanism can explain all the experimental observations activation parameters and the rate constant of the rate-determining step were calculated.